Waveform differential based pilot protection for transmission line connected to renewable energy sources. (July 2023) - Jia, Ke; Wen, Zhiwen; Bi, Tianshu; Wu, Tonghua; Zhang, Yang; Kong, Fanzhe; Yu, Lei
Highlights: It is demonstrated that the difference of short-circuit current characteristics between renewable energy sources and synchronous generators. The pilot protection based on Canberra distance is less affected by short-circuit current amplitude and abnormal data, and has good applicability in scenarios with the weak output of renewable energy sources. The protection based on waveform differential breaks through the limitation of power frequency and solves the problems faced by traditional differential protection. Abstract: Affected by the control objectives of the inverter, the short-circuit characteristics of renewable energy sources are quite different from those of traditional synchronous generators. As a result, the performance of traditional protection is degraded, and may lead to mis-operation and rejection, posing hazards for the safety of the power grid. In this research, the fault characteristics of renewable energy sources and traditional synchronous generators are analyzed and compared. Then, according to the difference between the fault transient current waveforms of two power sources, a pilot protection principle based on Canberra distance is proposed. Considering the phase angle error and amplitude error during normal operation, the protection constant is theoretically set to 0.35. Simulations and field experiments show that the protection principle reliably distinguishes the faults inside and outside the zone in different scenarios. The protection is less affected by short-circuit current amplitude and abnormal data, because the numerator of Canberra distance signifies the difference between the transient current waveforms and denominator normalizes the difference. In addition, the Canberra distance is 1 when the output of renewable energy sources is 0, so the proposed protection is also applicable to the scenario where the renewable energy sources output is 0.